Impact of health education on soil-transmitted helminth infections in schoolchildren of the Peruvian Amazon: a cluster-randomized controlled trial. - Theresa W Gyorkos; Mathieu Maheu-Giroux; Brittany Blouin; Martin Casapia (Public Library of Science (PLoS), 2013)
To control soil-transmitted helminth (STH) infections, the World Health Organization recommends school-based deworming programs with a health hygiene education component. The effect of such health hygiene interventions, however, has not been adequately studied. The objective of the present study was to determine the effectiveness of a health hygiene education intervention on the occurrence of STH re-infection four months post-de-worming.An open-label pair-matched cluster-randomized trial was conducted in Grade 5 schoolchildren of 18 primary schools (9 intervention and 9 control) in the Peruvian Amazon. Baseline assessment included interview with a pre-tested questionnaire and collection of single stool specimens that were examined using the single Kato-Katz thick smear. All schoolchildren were then treated with single-dose albendazole (400 mg). Schoolchildren in intervention schools then received 1) an initial one hour in-class activity on health hygiene and sanitation and 30-minute refresher activities every two weeks over four months; and 2) a half-day workshop for teachers and principals, while children in control schools did not. Four months later, STH infection was re-assessed in all schools by laboratory technologists blinded to intervention status. From April 21-October 20, 2010, a total of 1,089 schoolchildren (518 and 571 from intervention and control schools, respectively) participated in this study. Intervention children scored significantly higher on all aspects of a test of STH-related knowledge compared with control children (aOR = 18·4; 95% CI: 12·7 to 26·6). The intensity of Ascaris lumbricoides infection at follow-up was statistically significantly lower (by 58%) in children in intervention schools compared with children in control schools (aIRR = 0·42; 95% CI = 0·21 to 0·85). No significant changes in hookworm or Trichuris trichiura intensity were observed.A school-based health hygiene education intervention was effective in increasing STH knowledge and in reducing Ascaris lumbricoides infection. The benefits of school-based periodic deworming programs are likely to be enhanced when a sustained health hygiene education intervention is integrated into school curricula.